Comparison of the Effects of Peppermint Aromatherapy and Intravenous Ondansentron on The Incidence of Postoperative Nausea and Vomiting (Ponv) Laparotomy with General Anesthesia - Wulandari, Riani; Wijaya, Dadik Wahyu; Nasution, Akhyar Hamonangan (Asian Journal of Pharmaceutical Research and Development, 2021)
Background: Postoperative nausea and vomiting is known as Post Operative Nausea And Vomiting (PONV). Postoperative nausea and vomiting (PONV) is multifactorial and is strongly influenced by physiological factors. PONV was defined as nausea and/or vomiting occurring 24 hours postoperatively. Non-pharmacological/complementary therapies that can be used to prevent and reduce postoperative nausea and vomiting include aromatherapy. Peppermint aromatherapy can be a quick onset alternative to antiemetic therapy and is easy to administer. Objective: The purpose of this study was to determine the difference between the effects of peppermint aromatherapy and intravenous ondansetron on the incidence of postoperative nausea and vomiting (PONV) laparotomy with general anesthesia at H. Adam Malik General Hospital Medan and Network Hospital. Methods: This study is a clinical trial and uses a double-blind randomized controlled trial study design on subjects who underwent laparotomy surgery under general anesthesia at Haji Adam Malik Hospital and Network Hospital with 36 people with patients aged 18-65 years with ASA 1 and 2 physical status. who underwent laparotomy surgery under general anesthesia. Results: Statistically, there was a significant difference in PONV scores between the peppermint and ondansetron groups occurring at time T1 (15 minutes after treatment), where the p-value <0.05. Meanwhile, at times T0, T2, T3, there was no statistically significant difference in the PONV scores between the two groups, where the p-value> 0.05. Conclusion: Peppermint aromatherapy was better at reducing postoperative laparotomy with general anesthesia than standard intravenous 4 mg of ondansetron therapy, especially in the early minutes after surgery.